Water treatment unit processes - Stevenson, David (Imperial College Press, 1998)
Includes index.; This book is divided into three sections: the first reviews the main processes available for treating water for drinking (potable) purposes, the second goes into some detail about the design and operation of the non-filtration (clarification) processes, and the third deals exclusively with filtration and related applications. It is intended as a source of practical information rather than a theoretical research treatise and includes discussion of component parts of the process units with reasons for design features as well as operating principles.